Development of student worksheets in natural and social sciences based on culturally responsive teaching for fifth grade elementary students - Riswanti, Nova; Prehadini, Tampi; Senen, Anwar (Jurnal Penelitian Ilmu Pendidikan, 2024)
This study aims to determine the development and feasibility of student worksheets in natural and social sciences based on culturally responsive teaching for fifth grade elementary school students. This study is a development study using the ADDIE (Analysis, Design, Development, Implementation, Evaluation) development model. The research subjects were media experts, subject matter experts, teachers, and students. The research instruments were interviews, observations, needs analysis questionnaires, validation questionnaires, and teacher and student response questionnaires. Data analysis techniques used descriptive analysis. The results of the study indicate that worksheet products based on culturally responsive teaching are feasible and practical as teaching materials to support the learning process. Feasibility based on the results of subject matter expert validation obtained a total score of 96 in the very feasible category, while the results of media expert validation obtained a total score of 98 in the very feasible category. Practicality based on teacher response questionnaires and student response questionnaires was in the very practical category.